Systematic review: the role of the gut microbiota in chemotherapy‐ or radiation‐induced gastrointestinal mucositis – current evidence and potential clinical applications. Issue 5 (11th July 2014) - Touchefeu, Y.; Montassier, E.; Nieman, K.; Gastinne, T.; Potel, G.; Bruley des Varannes, S.; Le Vacon, F.; de La Cochetière, M. F.
Summary Background Gastrointestinal mucositis is defined as inflammation and/or ulcers of the gastrointestinal tract occurring as a complication of chemotherapy and radiation therapy, and affects about 50% of all cancer patients. Aim To assess the role of gut microbiota in the pathogenesis of gastrointestinal mucositis and the potential for manipulations of the microbiota to prevent and to treat mucositis. Methods Search of the literature published in English using Medline, Scopus and the Cochrane Library, with main search terms 'intestinal microbiota', 'bacteremia', 'mucositis', 'chemotherapy‐induced diarrhoea', 'chemotherapy‐induced mucositis', 'radiotherapy‐induced mucositis'. Results The gut microbiota plays a major role in the maintenance of intestinal homoeostasis and integrity. Patients receiving cytotoxic and radiation therapy exhibit marked changes in intestinal microbiota, with most frequently, decrease in Bifidobacterium, Clostridium cluster XIVa, Faecalibacterium prausnitzii, and increase in Enterobacteriaceae and Bacteroides. These modifications may contribute to the development of mucositis, particularly diarrhoea and bacteraemia. The prevention of cancer therapy‐induced mucositis by probiotics has been investigated in randomised clinical trials with some promising results. Three of six trials reported a significantly decreased incidence of diarrhoea. One trial reported a decrease in infectious complications. Conclusions The gut microbiota may play a major role in the pathogenesis of mucositis through the modification of intestinal barrier function, innate immunity and intestinal repair mechanisms. Better knowledge of these effects may lead to new therapeutic approaches and to the identification of predictive markers of mucositis.